Teaching African American Women’s Writing
XII, 220 p.
Keywords: The essays in Teaching African American Women's Writing provide reflections on issues, problems and pleasures raised by studying the texts. They will be of use to those teaching and studying African American women's writing in colleges, universities and adult education groups as well as teachers involved in teaching in schools to A level.